Four Unruly Women: Stories of Incarceration and Resistance from Canada’s Most Notorious Prison - Rech, Nathalie (Labour / Le Travail, 2020)
The article reviews the book, "Four Unruly Women: Stories of Incarceration and Resistance from Canada’s Most Notorious Prison," by Ted McCoy.